Cutaneous Metastasis as the Presenting Sign of Urothelial Carcinoma - Moreno de Oliveira Fernandes, Tânia Rita (2020)
Cutaneous metastases of visceral neoplasms are rare conditions, and urothelial or transitional cell carcinomas are responsible for less than 1% of cases. We report the case of a 50-year-old male patient who progressively developed multiple cutaneous nodules on his head, abdomen, axilla, and groin, some with ulceration. Skin biopsy and immunohistochemistry were consistent with cutaneous metastasis of urothelial carcinoma. Computed tomography scan revealed generalized metastasis in internal organs. In this rare case, cutaneous metastases were the presenting sign of the disease and, as reported, a sign of bad prognosis.